Biomechanical analysis of foot contact in junior sprinters - Hugo, Elmie (University of the Free State, 2011)
The purpose of this study was to determine the effects of different foot types (normal, flat and high arch) with regards to speed, roll-over and impact forces, thus attempting to indicate if a specific foot type is dominant amongst sprinters. The different foot types of ten junior sprint athletes and ten nonsprinters were determined by walking over a pressure platform (RSscan International’s Footscan® 7.x plate system). The effects of foot roll-over and peak pressures during sprinting were determined for left and right feet respectively. The subjects ran barefoot at their top speed (sprinted) over 20 meters, crossing a pressure platform (RSscan International’s Footscan® 7.x plate system) comprising the last two meters of the 20 meter distance. The initial contact, final contact, time to peak pressure and the duration of contact of the different sub-areas of the foot were measured. The results of the sprinters’ trials were averaged and compared to the non-sprinters’ averaged trials by performing a statistical T-test. The control group (non-sprinters) dominantly has a high arch foot type for both feet. In the sprinter group, the different foot types are all represented almost equally with regards to right feet, whereas the left feet are dominantly normal type, followed by high arch and then flat foot types. There was a significant difference (p < 0.05) during the Foot flat phase (FFP) between the sprinter group (mean left: 4.04ms, mean right: 4.34ms) and control group (mean left: 26.40ms, mean right: 24.46ms), left: p=0.007; right: p=0.022. This indicates that the FFP time is significantly faster for the sprinter group than for the control group. The control group spent a higher percentage of time on the rear foot than the sprinters did (left: p=0.0057, right: p=0.0268). The control group’s peak plantar pressures were predominantly on the sub-areas of the heel (mean:HL=Left: 327.69, right: 351.44; mean HM= Left: 434.08, right: 423.19) and M1, M2, M3, whereas the sprinters’ peak plantar pressures are predominantly on the subareas of the M1, M2, M3, mid-foot and T1, meaning that sprinters predominantly have peak pressures on forefoot contact whereas the nonsprinters predominantly have peak pressures on heel contact. The results of this study therefore indicate that in general, sprinters dominantly have a normal foot type whereas the non-sprinters have a high arch foot type, and sprinters predominantly have peak pressures on forefoot contact whereas the non-sprinters predominantly have peak pressures on heel contact during sprints.

Die doel van die studie was om die effek van verskillende voetsoorte (normaal, plat of hoë voetbrug) ten opsigte van spoed, voet bewegingspatroon en piekdrukking te bepaal, ten einde te poog om vas te stel of daar ’n spesifieke voetsoort is wat dominant is onder naellopers. Die voetsoort van tien junior naellopers en tien nie-naellopers (kontrole groep) is bepaal deur oor ’n drukplaat (RSscan International’s Footscan® 7.x plaatsisteem) te stap. Die effek van die bewegingspatroon en piekdrukking van die voet gedurende naellope is vir die linker- en regtervoet afsonderlik bepaal. Die toetsgroep het kaalvoet teen hul maksimale spoed oor ’n afstand van 20 meter gehardloop waarvan die laaste 2 meter die RSscan International’s Footscan® 7.x plaat-sisteem ingesluit het. Die aanvanklike kontak, finale kontak, tydsduur tot piekdrukking en die tydsduur van kontak van die verskillende subareas van die voet is gemeet. Die naellopers se gemiddelde proeflopies is deur ’n statistiese T-toets vergelyk met dié van die nienaellopers. Die kontrolegroep het ’n dominante hoë linker- en regtervoetbrug. Die naellopers se regtervoetsoort is eweredig versprei tussen die verskillende tipes voetsoorte terwyl die linkervoete dominant normaal is, gevolg deur hoëen laebrug voetsoorte. Daar was ’n noemenswaardige verskil (p < 0.05) tussen die naellopers (gemiddeld links: 4.04ms, gemiddeld regs: 4.34ms) en die kontrolegroep (gemiddeld links: 26.40ms, gemiddeld regs: 24.46ms) , links: p=0.007; regs: p=0.022, gedurende die Voet plat fase (VPF). Dit dui dus aan dat die naellopers se VPF tyd aansienlik vinniger as die kontrolegroep se tyd is. Die kontrolegroep het ’n hoër persentasie tyd op die agtervoet spandeer in vergelyking met die naellopers (links: p=0.0057, regs: p=0.0268). Die kontrolegroep se piek plantardrukking was hoofsaaklik op die subareas van die hak (gemiddeld:HL=links: 327.69, regs: 351.44; gemiddeld HM= links: 434.08, regs: 423.19) en M1, M2, M3. Daarteenoor was die naellopers se piek plantardrukking hoofsaaklik op die subareas van die M1, M2, M3, midvoet, en T1 uitgeoefen. Dit toon aan dat naellopers hoofsaaklik voorvoet piekdrukking tydens kontak uitoefen terwyl die kontrolegroep hoofsaaklik hak piekdrukking uitoefen. Die resultate van hierdie studie dui gevolglik aan dat naellopers oor die algemeen meestal ’n normale voetsoort het, terwyl die voete van die nie-naellopers deur ’n hoë voetbrug gekenmerk word. Die naellopers handhaaf ook oorwegend voorvoetkontak en – piekdrukking, in teenstelling met die kontrolegroep wat oorwegend hak piekdrukking handhaaf gedurende naellope.
Dissertation (M.A. (Exercise and Sport Sciences))--University of the Free State, 2011
Keywords: RSscan International; Non-sprinters; Sprinters; Barefoot sprinting; Foot roll-over; Peak pressures; Foot types; Sprinting; Running -- Physiological aspects; Running speed; Foot -- Movements